1974
DOI: 10.1161/01.res.35.6.883
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Physical Training on the Heart of Dogs

Abstract: To investigate the effects of physical training on cardiac dimensions and function, eight dogs were exercised for 12 weeks by treadmill running 1 hour/ day, 5 days/week. Five dogs were confined in cages as controls for an 8-week period. Heart rates were monitored by telemetry during rest and exercise. Maximum QRS spatial magnitudes were calculated from records of McFee lead electrocardiograms. Left ventricular end-diastolic dimensions were determined radiographically by the bead and clip technique. No statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1

Year Published

1976
1976
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 12 publications
5
34
1
Order By: Relevance
“…Wyatt and Mitchell noted an increase in end-diastolic left ventricular wall thickness and in the maximum QRS magnitude in dogs exercised on a treadmill over a 12 week period. 47 Our data are consistent with the views of Grande and Taylor32 who proposed that "physiological hypertrophy" of the heart represents a useful mechanism of adaptation in the athlete. Compared to the tall control group, mean Vcf and ejection fraction in this group of athletes showed no difference despite the lower heart rate of the athletes which tends to reduce mean Vcf.48' 1 In addition, the values for mean Vcf were within the previously published range of normal'5 and were consistent with the data obtained in a recent study using young, normal volunteers.…”
Section: Echocardiographic Studiessupporting
confidence: 92%
“…Wyatt and Mitchell noted an increase in end-diastolic left ventricular wall thickness and in the maximum QRS magnitude in dogs exercised on a treadmill over a 12 week period. 47 Our data are consistent with the views of Grande and Taylor32 who proposed that "physiological hypertrophy" of the heart represents a useful mechanism of adaptation in the athlete. Compared to the tall control group, mean Vcf and ejection fraction in this group of athletes showed no difference despite the lower heart rate of the athletes which tends to reduce mean Vcf.48' 1 In addition, the values for mean Vcf were within the previously published range of normal'5 and were consistent with the data obtained in a recent study using young, normal volunteers.…”
Section: Echocardiographic Studiessupporting
confidence: 92%
“…1,17 Echocardiographic measurements in dogs are reportedly affected by breed, 24 body weight, 12,25 age 26 and athletic training. 27 Unlike dogs, variations in cardiac size among the different horse breeds have not been investigated comprehensively. 8 Slater and Herrtage, 19 based on cardiac dimensions obtained in ponies and Thoroughbred foals, suggested that it may not be possible to predict normal values for equine cardiac dimensions from the data derived from multiple breeds.…”
Section: Discussionmentioning
confidence: 99%
“…The animals exercised 5 d/wk for 32 wk after an initial 1-2-wk period of graded exercise (12). Two dogs were excluded from the project due to inadequate performance in this initial period.…”
Section: Methodsmentioning
confidence: 99%